Validation Study of the 10-item Connor-Davidson Resilience Scale Among Mexican Medical and Psychology Students [Estudio de validación de la escala de resiliencia de Connor-Davidson de 10 ítems entre estudiantes de medicina y psicología mexicanos] - Daniel-González, Leopoldo (2020)
ABSTRACT The factorial structure, reliability, convergent and discriminant validity, as well as factorial invariance of the 10-item Connor-Davidson Resilience Scale (CD-RISC-10) were determined. The sample was composed of 330 students (174 medical students and 156 psychology students) with a mean age of 20.20 years (SD = 2.33). The results obtained confirm the unidimensional structure of the scale (χ2/df = 3.06, GFI = .93, CFI = .92, NFI = .90, TLI = .92, RMSEA = .08, and SRMR = .04), the factorial invariance with respect to career, and good internal consistency (ω = .85 and α = .85). A statistically significant difference in the level of resilience between medical students (M = 20.64, SD = 4.48) and psychology students (M = 20.27, SD = 4.51) was found [t(281) = 2.65, p = .009, d = .20]. Evidence of convergent and discriminant validity of CD-RISC10 with happiness and perceived stress was obtained. It is concluded that CD-RISC-10 shows adequate psychometric properties to measure resilience in Mexican university students.